METHOD DEVELOPMENT AND VALIDATION OF A STABILITYINDICATING RP-HPLC METHOD FOR ANALYSIS OF MELOXICAM USING DAD DETECTOR - Wali, Adil F.; Masoodi, Mubashir H.; Akbar, Mohd.; Mushtaq, Ahlam (Asian Journal of Pharmaceutical Research and Development, 2013)
A simple, precise and accurate isocratic RP-HPLC method was developed and validated for determination of Meloxicam in bulk drug and tablets. Isocratic RP-HPLC separation was achieved on a LiChrospher RP-18 column (250 x 4.6 mm id, 5 micron particle size) using the mobile phase ‘A’ 0.1 M dipotassium hydrogen phosphate pH 4.0 with orthophosphoric acid and mobile phase ‘B’ Methanol . Mobile phase ‘A’: mobile phase ‘B’ premixed in the ratio of 65:35 v/v were used as mobile phase at a flow rate of 1.0 mL/min and the column oven temperature was 35 ˚C good. The retention time of Meloxicam (2H-1, 2-benzothiazine- 3-carboxamide, 4-hydroxy-2-methy-N-(5-methyl-2-thiazolyl)-, 1, 1-dioxide) was about 4.31 min and its known impurity-B (5- methylthiazole-2ylamine) was about 2.26. The photodiode array detector was used to test the purity of the peaks, and the chromatograms were extracted at 254 nm. The method was validated for linearity, precision, accuracy, robustness, solution stability, and specificity. The method was linear in the concentration range of 150-450 µg/ml with a correlation coefficient of 0.999. The limit of detection (LOD) and limit of quantification (LOQ), respectively were 5 and 50 µg/mL for Meloxicam. The accuracy (recovery) was found to be in the range of 98.57%-101.69%. The drug was subjected to the stress conditions hydrolysis, oxidation, photolysis, and heat. Degradation products produced as a result of the stress conditions did not interfere with detection of Meloxicam; therefore, the proposed method can be considered stability-indicating.